Nisin damages the septal membrane and triggers DNA condensation in methicillin-resistant Staphylococcus aureus - Jensen, Camilla (2020)
Nisin is applied as a food preservative in processed foods and has the potential to be used synergistically with antibiotics for treatment of patients infected by antibiotic-resistant bacteria, such as methicillin-resistant Staphylococcus aureus. The present study explores the antimicrobial effect of nisin on S. aureus viability and membrane integrity and, for the first time, used super-resolution microscopy to study morphological changes induced in S. aureus cells exposed to nisin. The exposure of S. aureus to nisin caused membrane depolarization and rapid killing. Super-resolution structured-illumination microscopy and transmission electron microscopy confirmed that nisin damages the cellular membrane and causes lysis of cells. Strikingly, condensation of chromosomal DNA was observed in all cells exposed to nisin, a phenotype not previously reported for this compound. Moreover, cells exposed to nisin were significantly smaller than non-exposed cells indicating the emergence of cell shrinkage. The strong association of DNA condensation with nisin exposure indicates that nisin interferes with chromosome replication or segregation in S. aureus.